Ο πόλεμος φθοράς και η τακτική της εξαπάτησης και του αιφνιδιασμού στις πολεμικές επιχειρήσεις του Βυζαντίου (11ος-13ος αι.) - ΚΑΝΕΛΛΟΠΟΥΛΟΣ, Νικόλαος Σ. (Byzantina Symmeikta, 2022)
Theory (as attested by the military manuals) and practice prove that attrition warfare and the associated military tactics of deception and surprise played an important role in the byzantine military history. The paper studies cases of attrition warfare and surprise attacks exercised by the Byzantines from 11th till 13th century. Important military leaders such as Alexios I Komnenos were masters of attrition warfare and used skillfully that strategy whenever an open battle against a strong opponent was very precarious. The Byzantines took advantage of the Balkan and Asia Minor mountainous terrain as well as the recruitment of foreign fast moving troops armed with long range shooting weapons that facilitated the exercise of tactics of deception and surprise. These military tactics were mostly successful against the Latins while were occasionally successful against the Seljuks and the Turkomans. The paper concludes that attrition warfare and the tactics of deception and surprise were more often applied during the 13th century –a period that Byzantium’s military resources and capabilities diminished– thus being a distinctive byzantine method of warfare and gave rise to an active role of the infantry who under special circumstances could threaten the western cavalry.